Electrical microgrids powered by Solar Energy - Arrelucea Arana , Manuel Alexander (2023)
The article explores the evolution of energy sources from biomass to today's sustainable ones, emphasizing the historical relationship between humans and nature. Although coal drove the Industrial Revolution, with negative impacts, the current global priority is the transition to more sustainable energies. It suggests the use of distributed microgrids to generate energy, promoting investments in renewables and providing financial and socioeconomic benefits. Microgrids, essential in smart grids, optimize reliability and costs, managing hybrid sources and storage. Efficient integration of solar energy in microgrids is crucial, backed by research with neural networks. Direct current microgrids represent a breakthrough. From the financial perspective, rural electrification and solar "soft technology" are analyzed, with emphasis on the influence of "Startups" (a newly created company that, thanks to its scalable business model and the use of new technologies, has great growth possibilities) in decarbonization, as for example, in India, where the use of photovoltaic panels has been tested with good results. Accurate prediction of solar irradiance using recurrent neural networks is vital for optimizing solar microgrids, with a focus on remote communities. In summary, the article highlights the current importance of the transition to sustainable sources, proposing approaches to technical, financial and socioeconomic challenges, with emphasis on microgrids and energy management.